A review of methamphetamine use and stroke in the young - Hemphill, Kafi; Tierney, Shannon; Tirschwell, David; Davis, Arielle P. (Frontiers in Neurology, 2024)
Methamphetamine (meth) is a potent and addictive central nervous system stimulant with increasing use. Stroke is one severe possible complication of meth use. Due to high levels of manufacturing in Mexico, the western United States has experienced greater consequences of meth use. The literature reviewed herein is comprised of case studies and series, and it suggests that hemorrhagic stroke (including hypertensive-like intracerebral hemorrhage and aneurysmal subarachnoid hemorrhage), as opposed to ischemic stroke, is the more common type of neurovascular complication of meth use. Meth-related strokes are a particular concern for younger patients with stroke and may be a partial explanation for increasing stroke rates in this age group. We describe two cases (one intraparenchymal hemorrhage and one ischemic stroke) in young patients (<50 years old) with recent meth use to illustrate clinical characteristics and therapeutic considerations. There are several proposed pathophysiological explanations for methassociated hemorrhagic stroke including an induced hypertensive surge, vasospasm, blood brain barrier breakdown, chronic hypertension, aneurysm development and rupture, and very rarely associated vasculitis. The increased risk of ischemic stroke related to meth use is less well supported in the literature, but this may, in part, be related to a lack of appropriately designed and powered research studies. Proposed mechanisms for ischemic stroke complications of meth use include those affecting blood vessels such as accelerated atherosclerosis, chronic hypertension, vasospasm, and vasculitis, plus mechanisms that affect the heart including cardiomyopathy, arrhythmias, and infective endocarditis (especially with injection drug use). Standard therapeutic interventions for acute stroke and approaches to secondary stroke prevention seem appropriate for meth-associated strokes, with the addition of abstinence from continued meth use. There is no evidence for any meth-specific stroke treatments. Finally, the prolonged duration of meth withdrawal is described. Larger, prospective studies of meth-related strokes are needed to allow for a better understanding and improved care for this often-devastating consequence of an increasingly prevalent cause of strokes in young patients.